Redes definidas por software com serviços orientados a nomes - Lucas Augusto Maia da Silva (2016)
SDN proposes the separation of the control plane from the data plane, allowing a programmable and logically centralized control plane. OpenFlow has been proposed as a standard for the implementation of an SDN architecture. Despite its success, OpenFlow has its limitations. For example, it lacks the capability to support higher network layer elements during network processing. Our project aims to expand the abstraction power of OpenFlow, providing new matching rules. We extend OpenFlow to support Domain Names matching rules. Our system allows the creation of forwarding rules using domain names. Our system allows to easily implement applications such as firewall and a QoS application. We built a prototype switch and a controller that can handle the domain name extension. Our approach provides a higher abstraction to program the network. We believe our proposal can bring interesting innovations to the OpenFlow protocol and to the future of SDN.